Correlation between perimenopausal syndromes and depression in nurses at Sanglah General Hospital - Ni Wayan Dewi Putriny Asih; Ni Ketut Sri Diniari; Cokorda Bagus Jaya Lesmana; Luh Nyoman Alit Aryani; Anak Ayu Sri Wahyuni (Indoscholar Publication and the Indonesian Psychiatric Association, 2020)
Background: Perimenopause covers the period immediately before the menopause and the first year after the last menstrual period. In addition to the changes in the menstrual cycle, women in the perimenopause phase often report a number of perimenopausal complaints and depressive disorders. This study aims to determine the prevalence of perimenopausal complaints and depression experienced in nurses at Sanglah General Hospital. Methods: The study uses a cross-sectional analytical. The measurement of perimenopause complaints uses the Menopause Rating Scale (MRS) questionnaire and the depression measurement uses the Beck Depression Inventory-II questionnaire (BDI-II). The data are analyzed descriptively, it uses the Fisher test and linear regression test with significance level p <0.05. Results: Nurses who have perimenopausal complaints are 62.7%. Besides, depression is experienced by 23.8% of nurses who have perimenopausal complaints. The complained somatic symptoms with a mild degree are 50% and moderate degree is 40%. While the urogenital sexual symptoms with a moderate degree are 60%, and mild and severe degrees are 20%. Conclusion: This study shows the relationship between perimenopausal complaints and the depression of the nurses in Sanglah General Hospital. Therefore, it is necessary to hold an early detection of depression prevention by screening perimenopausal complaints.